PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN INDUSTRI DASAR & KIMIA DAN INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Finda, Lo; Panjaitan, Fery; Ruben Manullang, Rizal (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
This is a bachelor thesis compiled by Lo Finda, student identification number 130150071, titled in Indonesian: "Pengaruh Profitabilitas, Ukuran Perusahaan dan Likuiditas terhadap Struktur Modal pada Perusahaan Industri Dasar & Kimia dan Industri Barang Konsumsi di Bursa Efek Indonesia Periode 2013-2017". This research was conducted in February to June 2018 in the city of Pangkalpinang. The purpose of this study was to determine the effect of Profitability, Company Size and Liquidity on Capital Structure both partially and simultaneously, in the companies of Basic Industry & Chemical and Consumer Goods Industry 2013-2017. This study uses quantitative data analysis, multiple linear regression and determination using secondary data. The test results using multiple regression show a sig value of 0.000 <0.05, which means that profitability has an effect on the capital structure of the Basic & Chemical Industry companies and the Consumer Goods Industry listed on the Indonesia Stock Exchange for the period 2013-2017. The test results using multiple regression show sig value 0.006 <0.05, which means that profitability affects the capital structure. The test results using multiple regression show sig value 0.034 <0.05, which means that the size of the company influences the capital structure. The test results using multiple regression show a sig value of 0.001 <0.05, which means that liquidity has an effect on the capital structure of the Basic & Chemical Industry companies and the Consumer Goods Industry listed on the Indonesia Stock Exchange for the period 2013-2017. Simultaneous test results show Fcount (62.53)> Ftable (2.81), thus also if comparing significant values ​​of 0.001 <0.05 which means Profitability, Company Size and Liquidity together or simultaneously have a significant effect on Structure Capital.